The Impact of adventure-based training on team cohesion and psychological skills development in elite sporting teams - Boyle, I.
Meyer & Wenger (1998) and Meyer (2000) were instrumental in pioneering research into the efficacy of adventure-based training with sporting teams. This investigation adds to the growing body of knowledge in this area by demonstrating the positive effects an adventure training intervention has on athletes` ability to learn new team and psychological skills. Quantitative measures investigated the development of team cohesion among elite netball players during their national season. In three of four team-cohesion sub-scales ATG-T, ATG-S, and GI-T significant differences were noted between the treatment and control groups. These significant results were supported by the athletes` qualitative accounts of the intervention.In qualitative terms, focus group and one on one phenomenological interviews were triangulated against observational and statistical data to help build a picture of the athletes` experience. In the phenomenological tradition, obtaining the athletes` perspective of the intervention was most important. With this in mind, both the outcomes and the process that led to the outcomes were documented.